Presencia de Serapias vomeracea Briq. (Orchidaceae) en Córdoba (Andalucía, España) - Carpintero Ortega, Soledad; Cano Villegas, Francisco Jesús (Acta Botanica Malacitana, 2020)
Se confirma la presencia de Serapias vomeracea en la provincia de Córdoba (España).